Extracorporeal shock wave lithotripsy: an opinion on its future : symsposium - Rassweiler, Jens; Rassweiler-Seyfried, Marie-Claire; Frede, Thomas; Alken, Peter (Indian journal of urology, 2014)
The development of miniaturized nephroscopes which allow one-stage stone clearance with minimal morbidity has brought the role of shock wave lithotripsy (SWL) in stone management into question. Design innovations in SWL machines over the last decade have attempted to address this problem. We reviewed the recent literature on SWL using a MEDLINE/PUBMED research. For commenting on the future of SWL, we took the subjective opinion of two senior urologists, one mid-level expert, and an upcoming junior fellow. There have been a number of recent changes in lithotripter design and techniques. This includes the use of multiple focus machines and improved coupling designs. Additional changes involve better localization real-time monitoring. The main goal of stone treatment today seems to be to get rid of the stone in one session rather than being treated multiple times non-invasively. Stone treatment in the future will be individualized by genetic screening of stone formers, using improved SWL devices for small stones only. However, there is still no consensus about the design of the ideal lithotripter. Innovative concepts such as emergency SWL for ureteric stones may be implemented in clinical routine.